2007
DOI: 10.3892/ijo.31.6.1339
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4a immunocytochemistry in liquid-based cervical cytology: is it feasible for clinical use?

Abstract: Abstract.A consecutive series of 118 samples from patients referred to colposcopy assessment and follow-up with cytology and biopsies were analysed with immunocytochemical staining to determinate the expression of p16 INK4a . Accumulation of p16INK4a antigen has been proposed as a biomarker helpful for the identification of dysplastic cervical cells. In our study all benign cases were negative for p16 INK4a , while more than half of the high grade lesions showed moderate or strong reactivity. There was a cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Furthermore, Ki-67 and/or p16 INK4A expression have been found to be markers of progression for intraepithelial neoplastic lesions in cervix, vulva, vagina, and anus ( Cameron et al , 2002 ; Norman et al , 2007 ). We observed a correlation between HPV positivity, lower histopathological grade, and high p16 INK4A expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Ki-67 and/or p16 INK4A expression have been found to be markers of progression for intraepithelial neoplastic lesions in cervix, vulva, vagina, and anus ( Cameron et al , 2002 ; Norman et al , 2007 ). We observed a correlation between HPV positivity, lower histopathological grade, and high p16 INK4A expression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other SCCs have shown that p16 INK4A expression measured by immunohistochemistry correlates well with HPV positivity ( Mellin Dahlstrand et al , 2005 ; Santos et al , 2006 ; Reimers et al , 2007 ; Fuste et al , 2010 ), making it a useful biomarker for HPV-related oncogenic activity and malignant transformation in cervix, vulva, and vagina ( Klaes et al , 2001 ; O'neill and Mccluggage, 2006 ; Fuste et al , 2010 ). In the cervix p16 INK4A has proven as useful in identifying dysplasia, and correlates with the severity of dysplasia ( Norman et al , 2007 ). In the cervix and other sites, it has also been demonstrated to be of prognostic significance ( Masoudi et al , 2006 ; Reimers et al , 2007 ; Schwarz et al , 2012 ).…”
mentioning
confidence: 99%